Examination of Entrepreneurship from Humanistic Values Perspective - Yilmaz, Ercan (Scientific Research Publishing, 2018)
This study attempts to examine the influence of humanistic values people prefer on their entrepreneurship. The study is a qualitative study and the data were collected and analyzed using this method. Besides, rela- tional screening model was used. The study group is composed of 482 students who were selected with random sampling method among students who attended various faculties at Selçuk University in 2012. In the study, Schwartz List of Values was used to measure individuals’ value preferences in their lives. En- trepreneurship Scale, which was developed by Yılmaz and Sünbül (2009), was used to measure their en- trepreneurship tendency. In the study, it was revealed that there is a significant relation between humanis- tic values people prefer and entrepreneurship and, humanistic values explain entrepreneurship tendency.
Keywords: Schwartz List of Values; Humanistic Values; Entrepreneurship; Component